Conventional-Microwave Mediated Synthesis and In Vitro Antimicrobial Activity of Novel Carbazole-Efflux Pump Inhibitor Hybrid Antibacterials. (6th November 2017) - Yaqub, Ghazala; Sadiq, Zubi; Hamid, Almas; Fatima, Amber; Ijaz, Zainab
Abstract : Work presented herein is the first report of two dual-action hybrids synthesized by covalent linkage of carbazole based novel antibacterial compounds with efflux pump inhibitors, that is, indole acetic acid/gallic acid. In this paper, novel antibacterial compounds 2 and 3 were prepared first and then these were covalently linked with efflux pump inhibitors, that is, indole acetic acid/gallic acid leading to the successful formation of two dual-action hybrids 4 and 5 . Prepared antibacterials and hybrids were evaluated for their bacteria cell killing capability against Escherichia coli, Staphylococcus aureus, Pasteurella multocida, and Bacillus subtilis. Both antibacterial compounds 2 and 3 were found effective against all tested bacterial strains at different concentrations. But when these compounds were linked with efflux pump inhibitors, they showed dramatic enhancement in their bacterial cell killing potential and minimum inhibitory concentration of all hybrids ranging from 7.250 μ g/mL to 0.05 μ g/mL. These prepared hybrid drugs will be promising and effective new agents in the category of dual-action antibiotics.